Immune cell metabolism in autoimmunity. (11th March 2019) - Teng, X; Li, W; Cornaby, C; Morel, L
Summary: Immune metabolism is a rapidly moving field. While most of the research has been conducted to define the metabolism of healthy immune cells in the mouse, it is recognized that the overactive immune system that drives autoimmune diseases presents metabolic abnormalities that provide therapeutic opportunities, as well as a means to understand the fundamental mechanisms of autoimmune activation more clearly. Here, we review recent publications that have reported how the major metabolic pathways are affected in autoimmune diseases, with a focus on rheumatic diseases. Graphical Abstract: